2019
DOI: 10.1108/scm-12-2017-0406
|View full text |Cite
|
Sign up to set email alerts
|

Additive manufacturing: empirical evidence for supply chain integration and performance from the automotive industry

Abstract: Purpose Additive Manufacturing offers much potential for industry, but at the same time is likely to have a significant impact on supply chain theory and practice. To-date there has been limited empirical work exploring the effect of Additive Manufacturing, and this study aims to provide a detailed appraisal of how supply chain integration, supply chain performance and firm performance may be affected by the adoption of Additive Manufacturing. These are critical factors for supply chain management, but have re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
81
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(87 citation statements)
references
References 76 publications
(152 reference statements)
3
81
0
3
Order By: Relevance
“…AM techniques are based on a manufacturing concept that is depositing sequentially layers of material until the part is complete [ 7 ]. Nowadays, 3D printing techniques are present in several industrial fields, for instance, the aeronautical industry [ 8 ], aerospace [ 9 , 10 ], naval [ 11 ], medical [ 12 , 13 ], or automotive industries [ 3 , 14 ]. It is perceptible that AM techniques mark a turning point for the manufacturing industry.…”
Section: Introductionmentioning
confidence: 99%
“…AM techniques are based on a manufacturing concept that is depositing sequentially layers of material until the part is complete [ 7 ]. Nowadays, 3D printing techniques are present in several industrial fields, for instance, the aeronautical industry [ 8 ], aerospace [ 9 , 10 ], naval [ 11 ], medical [ 12 , 13 ], or automotive industries [ 3 , 14 ]. It is perceptible that AM techniques mark a turning point for the manufacturing industry.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical research has been conducted to analyse AM's influence on the production processes and the increase in automotive supply chain management performance. This research found that the adoption of AM directly influences the performance of the automotive supply chain and the firm, while supply chain integration indirectly assists in performance improvements (Delic, Eyers, and Mikulic 2019). Another empirical research conducted by (Delic and Eyers 2020) focused on analysing AM adoption's impact on the production processes and automotive supply chain management's flexibility and performance.…”
Section: Am and Its Supply Chain Implicationsmentioning
confidence: 92%
“…The match between spare parts and AM is therefore clear and additively manufactured spare parts are already in use in some leading sectors, such as automotive and aviation, which has been reported in academic publications (Delic et al , 2019; Khajavi et al , 2018; Togwe et al , 2019) and prominent corporate press releases (Daimler AG, 2018; Satair, 2020; Volvo, 2018). However, although AM offers many advantages and the benefits are clearly presented in the literature, the use of AM in spare part production is still very limited in sectors outside of the spearhead due to a variety of barriers (Thomas-Seale et al , 2018).…”
Section: Introductionmentioning
confidence: 94%
“…The match between spare parts and AM is therefore clear and additively manufactured spare parts are already in use in some leading sectors, such as automotive and aviation, which has been reported in academic publications (Delic et al, 2019;Khajavi et al, 2018;Togwe et al, 2019) and prominent corporate press releases (Daimler AG, 2018;Satair, 2020;Volvo, 2018).…”
Section: Introductionmentioning
confidence: 96%